КӨРКЕМ ШЫҒАРМАЛАРДЫ ОҚЫТЫЎДА ОҚЫЎШЫЛАРДЫҢ ДӨРЕТИЎШИЛИК КОМПЕТЕНЦИЯСЫН ЖЕТИЛИСТИРИЎ - Қабулова, М.Т. (FAN va JAMIYAT, 2022)
The article focuses on improving the educational competence of students in the teaching of works of art. It was noted that the development of students’ speech culture and language skills through reading works of art.